2006
DOI: 10.1158/1078-0432.ccr-05-2732
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Colorectal Cancer Patients with Modified Vaccinia Ankara Delivering the Tumor Antigen 5T4 (TroVax) Induces Immune Responses which Correlate with Disease Control: A Phase I/II Trial

Abstract: Purpose: The highly attenuated strain of vaccinia virus, modified vaccinia Ankara (MVA), encoding the tumor antigen 5T4 (termed TroVax), has been evaluated in an open-label phase I/II study in colorectal cancer patients. The primary objectives were to assess the safety and immunogenicity of ascending doses of TroVax and to determine the biodistribution of the vector. Experimental Design: TroVax was given to 22 patients with metastatic colorectal cancer. Seventeen patients received doses of TroVax ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
107
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 23 publications
6
107
0
Order By: Relevance
“…Results from phase I and II clinical studies of MVA-5T4 in renal, colorectal, and prostate cancer patients were encouraging and showed that immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16). In particular, studies in RCC and colorectal cancer patients have detected an association between 5T4-specific (but not MVA) antibody responses and enhanced survival (9,12,16).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Results from phase I and II clinical studies of MVA-5T4 in renal, colorectal, and prostate cancer patients were encouraging and showed that immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16). In particular, studies in RCC and colorectal cancer patients have detected an association between 5T4-specific (but not MVA) antibody responses and enhanced survival (9,12,16).…”
Section: Discussionmentioning
confidence: 96%
“…These studies showed MVA-5T4 to be well tolerated and able to induce 5T4-specific immune responses in most patients. Furthermore, associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of the nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 96%
“…There are currently 2 5T4-targeting agents in clinical development for oncology indications: a vaccine consisting of 5T4-expressing vaccinia virus (26)(27)(28) and an anti-5T4 antibody fragment conjugated to superantigen from Staphylococcal enterotoxin A (29,30). Both of these agents engage the host immune system to attack the 5T4-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…11), also elicits robust nAb responses and confers protection against lethal monkeypox viral challenge via various routes (12,13), yet it has a much improved safety profile as compared with vaccinia virus (14)(15)(16)(17). Importantly, MVA is also being developed as a vaccine vector for many infectious and noncommunicable diseases (18)(19)(20)(21).…”
mentioning
confidence: 99%